The Doctrines of Shi'i Islam: A Compendium of Imami Beliefs and Practices - Subḥānī, Ǧaʿfar (I.B.Tauris, 2001)
This text offers a wide-ranging overview of the principal tenets of Shi'i Islam. It is useful not only as an introductory text on Shi'i thought and practice, but also as a contemporary expression, from within, of this branch of this vibrant branch of the Islamic faith. Comprehensive and concise, this work is principally theological and jurisprudential, dealing with such issues as the concept of knowledge, the nature of being and the problem of evil